2012
DOI: 10.2478/v10213-012-0015-3
|View full text |Cite
|
Sign up to set email alerts
|

Immunolocalisation of α and β Oestrogen Receptors in Basolateral Amygdala of Rabbit Males

Abstract: Expression of α (ER-α) and β (ER-ß) oestrogen receptors in neurons of basolateral complex of the amygdala was studied in rabbit males. The examinations were carried out on brains of 12 sexually mature rabbit males weighing 3-4 kg. An immunohistochemical method (IHC) with primary Er-α antibodies, NCL-L6F11 and Er-ß: NCL-ERbeta clone EMR02 was applied. The percentage of immunoreactive neurons was determined. Morphometric and statistical analysis of immunoreactive (ER+) neurons was carried out including the local… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Er-α in comparison to Er-β localised primarily in neuron cytoplasm. This difference was observed not only in PC but in other brain areas such as amygdale and hippocampus (11,15). The previous studies have shown that in PC, there are interneurons classified according to the expression of two types of cell markers (molecular markers) -calcium-binding proteins and neuropeptides (23).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Er-α in comparison to Er-β localised primarily in neuron cytoplasm. This difference was observed not only in PC but in other brain areas such as amygdale and hippocampus (11,15). The previous studies have shown that in PC, there are interneurons classified according to the expression of two types of cell markers (molecular markers) -calcium-binding proteins and neuropeptides (23).…”
Section: Discussionmentioning
confidence: 93%
“…Oestrogen hormones act on nerve tissue by means of receptors. The examinations performed on rabbits have proven that oestrogen receptors occur in structures of the amygdala in rabbit males (15). It refers to α-and β-oestrogen receptors.…”
Section: Introductionmentioning
confidence: 99%
“…Those rats also presented alterations in aromatase activity (Di Prisco, Lucarini, & Dessi-Fulgheri, 1978), which aromatizes T into estradiol (Moralí, Larsson, & Beyer, 1977;Muller, Van Den Beld, Van Der Schouw, Grobbe, & Lamberts, 2006) and activates sexual motivation. These hormones produce non-genomic effects in the neuronal membrane that modulates the electrical activity of neurons in several brain areas (del Río-Portilla, Ugalde, Juárez, Roldán, & Corsi-Cabrera, 1997;Joëls, 1997;Poblano et al, 2004;Balthazart, Baillien, Cornil, & Ball, 2004), including the medial prefrontal cortex (mPFC) and the basolateral amygdala (BLA), two cerebral structures that have androgen (Naghdi, Oryan, & Etemadi, 2003;Nuñez, Huppenbauer, McAbee, Juraska, & DonCarlos, 2003), estrogen (Montague et al, 2009;Lonc, 2012), and glucocorticoid (Pryce, 2008) receptors. The BLA has strong connections with the mPFC, especially layers II and V, in rodents (Cunningham, Bhattacharyya, & Benes, 2002).…”
Section: Introductionmentioning
confidence: 99%